HUBUNGAN KEJADIAN ENTEROBIASIS DENGAN KEPATUHAN IBU DALAM PEMBERIAN OBAT PADA ANAK DI DESA LAMBANG KUNING KABUPATEN NGANJUK - Siti Munawaroh; Wahyu Suryaningsih, Vivien Dwi Purnamasari (CV. Adiba Aisha Amira, 2024)
Enterobiasis is a disease caused by the worm Enterobius vermicularis. Clinical symptoms include restlessness at nightdue to itching intheanusdue to theactivity of adult female worms moving to the area to lay eggs and secondary infections around the anus due to scratching. Treatment is carried out with a frequency of once every 6 months. Adherence to taking deworming in children aged 6-10 years should be accompanied by parents and adjusted to medical instructions. The purpose of this study was tofind out the relationship between I bu's compliance in deworming and the incidence of Enterobiasis in children in The Yellow Emblem Village of Nganjuk Regency. Cross Sectional research design, a sampling technique using purposive sampling with a total sample of 20 respondents. The results of this study obtained 7 (35%) positive infected with Enterobius vermicularis and 13 (65%) negative not infected with Enterobius vermicularis. The results of filling out the questionnaire found that 11 (55%) mothers had a good level of compliance as much as 1 (5%) infected with Enterobius vermicularis, while 9 (45%) mothers had a non-compliance rate of 6 (30%) infected with Enterobius vermicularis. The results of the Chi Square test variable maternal adherence in the administration of deworming drugs with the incidence of Enterobiasis obtained a p-value of 0.007 which means less than 0.05, so it can be concluded that there is a relationship between maternal adherence in giving deworming drugs and the incidence of Enterobiasis in children in the yellow emblem village of Nganjuk.